Novos municípios como espaços sociais e políticos : implicações do processo de emancipação político-administrativa na mesorregião centro-ocidental do Paraná - Souza, Adalberto Dias de (2016)
This work had as objective to analyze the implications of the process of political emancipation, in municipalities in Mesoregion Paraná State Central Western, in the period 1988 to 2015. The process was analyzed as an element for transformation into new social and political spaces for its citizens. We researched from the city of origin seeking to bring a focus of it, as the institutionalization of local, as well as on the possibilities of this to consolidate the social space for citizens. At a later time we refer to the municipality in Brazil looking to focus on aspects related to centralization and decentralization of this federative entity, at different moments of Brazilian history from the colonial period to the republican period, after the promulgation of the Constitution of 1988. We also seek discuss the issue of taxes, in order to demonstrate that the municipality is not the main absorber of funds raised by the nation levied taxes. In sequence approach on the municipalities of Mesoregion Western Center Paranaense in order to demonstrate and analyze the implications of the administrative political emancipation process that took place in each of them and the prospects created by this process to the daily lives of citizens residing in these localities. We use national and international, theoretical framework within the Geography and Public Administration, as well as other sciences when necessary; Collect secondary data through the main Research Institutes in Brazil, as well as primary use information obtained through questionnaires and interviews conducted in the municipalities studied, with local pioneers, public officials and other citizens. The spatial area of research was the Mesoregion Western Center Paranaense and time frame, the period from 1988 to 2015. The sample was composed of four counties, two of the micro-region of Campo Mourao (Luiziana and Farol) and two micro-Goioerê (Quarto Centenário and Rancho Alegre d'Oeste). The procedures used indicated the relevance of municipal emancipations to the sites studied, as have shown that progress has been made, which translate into improvements of public facilities and services available to the population, thus providing significant social benefits for the local society, what consequently contributed for the progress of mesoregion West-Central of Paraná, in the social, economic and spatial.